Henry Bate's Tabule Machlinenses: the earliest astronomical tables by a Latin author. Issue 4 (2nd October 2018) - Nothaft, C. Philipp E.
ABSTRACT: The known works of the medieval astronomer/astrologer Henry Bate (1246–after 1310) include a set of planetary mean motion tables for the meridian of his Flemish hometown Mechelen. These tables survive in three manuscripts representing two significantly different recensions, but have never been examined for their principles of construction or underlying parameters. Such analysis reveals that Bate employed an unusual value for the length of the tropical year ( c. 365 1/4 − 1/112 days), which was probably derived by comparing ancient and contemporary observations of the vernal equinox. In addition, there are clear signs that Bate kept revising his parameters for the mean motions of Venus and the three superior planets, none of which can be traced back to earlier sources. Together with some of Bate's preserved statements, these findings support the conclusion that the Tabule Machlinenses were unique among the astronomical tables produced in medieval Latin Christendom for using independently derived parameters that were the result of new observations. Bate's achievement connects him to a wider milieu of astronomers operating in late-thirteenth-century Paris, who put an increased emphasis on observation and the critical examination of received data.